In presenza dell'autore: L'autorappresentazione come evoluzione della storiografia professionale tra basso Medioevo e Umanesimo - Fulvio Delle Donne (Testi: Antichità, Medioevo e Umanesimo, 2018)
This volume investigates how historiography became a "profession" from the 13th to the 15th century. As a genre, historiography is difficult to define: inspired by Cicero's rhetorical rules, humanists were the first to elaborate a specific ars. In doing so, they adapted rhetoric to a new ethical sense of humanitas. Several contributors to this book have already discussed in previous works of theirs the linguistic and rhetorical choices that some important historians made. See, for instance, Tra storiografia e retorica: prospettive nel basso medioevo italiano, ed. M. Zabbia, in «Reti Medievali. Rivista», 19 (2018), especially the papers by Paolo Garbini, Marino Zabbia, and Fulvio Delle Donne. On this occasion, they pay attention to the authors' direct interventions: their self-representation and reflections on methodological issues reveal a new consciousness, which gradually developed over the centuries. This volume is a part of the PRIN project (the acronym standing for Project of Relevant National Interest) titled "A.L.I.M. (Digital Archive of the Italian Latinity in the Middle Ages: http://www.alim.dfll.univr.it): Practices and theory for computer archiving and philology applied to medieval texts", which Professor Fulvio Delle Donne coordinates at the University of Basilicata.